Research on the Digital Transformation Strategy of Short Video Creation for Ideological and Political Teachers in Vocational Colleges - Jiajun Hu (Journal of Exploration of Vocational Education, 2025)
The rapid development of new-media technologies has triggered a structural transformation in the communication ecology of ideological and political education in vocational colleges, confronting the traditional nurturing model with the imperative of digital transformation. Taking the convergence of “short video + ideological and political education” as its entry point, this study focuses on how ideological and political teachers in vocational colleges—while shifting into the role of short-video bloggers—can enhance the quality and effectiveness of ideological and political education through innovations in content-production mechanisms, shifts in pedagogical discourse paradigms, and the construction of a dissemination-effectiveness evaluation system. By unpacking the mutually embedded logic between the communicative features of short videos and the laws of ideological and political education, the paper reveals the practical dilemmas and breakthrough pathways faced by teachers in reconstructing their digital identities, providing methodological insights for expanding the digital practice of ideological and political education.